2010
DOI: 10.29358/sceco.v0i15.107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Correlations Between Public Capital Investments and Economic Development in Romania

Abstract: Literature Review on the Correlation Between Public Capital Investments and Economic DevelopmentThe purpose of this literature review is to present a selection of studies and reports which show the positive and also the negative correlations between public capital investments and economic growth, studies that were based on results obtained in the respective countries. Discussions on the effects of infrastructure had increased especially after 1989, with the assumption made by David Alan Aschauer, that the decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A study on Belgium indicated a negative relationship between the rate of employment and expenditure on public capital (Everaert & Heylin 2004). An increase of 1% in this kind of public expenditure led to an increase in private sector unemployment of 0.32% (Sava & Zugravu 2010). In these cases, a relationship between public expenditure on capital and economic growth was found, but it was negative probably because of a crowding-out effect of private investments.…”
Section: Previous Research On the Topicmentioning
confidence: 92%
See 1 more Smart Citation
“…A study on Belgium indicated a negative relationship between the rate of employment and expenditure on public capital (Everaert & Heylin 2004). An increase of 1% in this kind of public expenditure led to an increase in private sector unemployment of 0.32% (Sava & Zugravu 2010). In these cases, a relationship between public expenditure on capital and economic growth was found, but it was negative probably because of a crowding-out effect of private investments.…”
Section: Previous Research On the Topicmentioning
confidence: 92%
“…They studied Chinese data over the period 1988-2007 and estimated output elasticities using Cobb-Douglas production functions, which they developed into a gross productive equation. Sava and Zugravu (2010) studied the correlation coefficients between infrastructure and national income for Romania using regression analysis over the period [2006][2007][2008][2009], and found a similar positive relationship, although not very strong. Higher government expenditure on capital thus also led to economic development in Romania.…”
Section: Previous Research On the Topicmentioning
confidence: 99%